The Assessing the effect of Business Intelligence and Innovation on business startups: A Case Study Approach - Saeed, Sarkar Ahmed; Faraj, Shahen Mohammed; Azam, Kosar Othman; Ali, Zhino Omer; Hussein, Sima Kakl (Fakultas Ekonomi Universitas Andalas, 2024)
business intelligence and innovation are crucial in initiating and advancing company enterprises. This research examined the impact of business intelligence and innovation on business startups. A simple random sampling approach was used to gather data using questionnaires mailed to 173 workers and managers of enterprises in the Kurdistan Region of Iraq. The study used Pearson correlation and Regression analysis to ascertain the association between factors and the impact of business intelligence and innovation on company startups. The analysis was conducted using SPSS software version 26. The study findings demonstrate a direct and positive relationship between the variables of business intelligence and innovation for business startups. Additionally, business intelligence and innovation have a noteworthy impact on the success of business startups.